A MODERN SURVEY ON PROBLEMS OF BUSINESS ORGANIZATION’S SECURITY: A MODERN SURVEY ON PROBLEMS OF BUSINESS ORGANIZATION’S SECURITY - Hristov, Hristo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Because of the intensification of the competitive environment, the question about having your own structure for counteractions against threats and encroachments on company security causes little and less rejection, misunderstanding and apprehension. In the current century this activity becomes a common occurrence in the sphere of business organizations. Its regular customer is a private sector that pays more attention to opportunities and more often uses the services of specialized complex unit responsible for counteraction against threats and encroachments on company security. In connection to this the report examines the current problems of business organizations concerning their security supply.